Pengaruh Model Picture and Picture dan Motivasi Siswa terhadap Keterampilan Menulis - Hafiiz, Al; Abdurahman (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2026)
This study investigated the effects of the Picture and Picture learning model and students’ learning motivation on fantasy story writing skills. A quantitative experimental method with a 2×2 factorial design was employed involving seventh-grade students at a junior high school in Padang, West Sumatra, Indonesia. The participants were divided into an experimental class taught using the Picture and Picture model and a control class taught through direct instruction. Students’ learning motivation was classified into high and low categories. Data were collected using a fantasy story writing test and a learning motivation questionnaire. The findings revealed that students taught through the Picture and Picture model achieved higher writing scores than those taught through direct instruction. Students with high learning motivation also performed better in writing activities than those with low motivation. However, no significant interaction was found between the instructional model and learning motivation. The study suggests that the Picture and Picture model effectively supports imagination and idea development in fantasy writing.